Individual Taxpayer Perceptions of the Implementation of the Digital Tax Administration System through (Coretax) in Supporting Tax Compliance: A Case Study in Merauke Regency, Indonesia - Semuel Batlajery; Mensy Otelyo Kastanya; Kaila Isabela Humaero (Journal of International Conference Proceedings, 2026)
This study aims to analyze individual taxpayers' perceptions regarding the implementation of Coretax. This study uses a descriptive qualitative research approach. The informants in this study were 10 individual taxpayers. The sampling technique used propositional sampling with the criteria being individual taxpayers who have a Taxpayer Identification Number (NPWP) and individual taxpayers who use the Coretax application . Data collection techniques used interviews, observation, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing techniques . The results of the study indicate that individual taxpayers have a positive perception of the implementation of Coretax, this system is able to provide easy access to tax services can increase taxpayer awareness, improve administrative efficiency, and is able to assist taxpayers in fulfilling their tax obligations. In addition, Coretax is also considered to support increased taxpayer compliance through ease of reporting and access to more integrated tax information. However, based on the results of the study there are obstacles including a lack of understanding of the new system users, technical disruptions that often still occur during use, difficulty understanding features, and lack of socialization. Overall, the implementation of Coretax makes a positive contribution in supporting individual taxpayer compliance in Merauke RegencyKeywords: Coretax;taxpayer perception;tax compliance;tax digitalization; individual taxpayers